At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
(- 1, - 3 )
Step-by-step explanation:
Given the 2 equations
2x + y = - 5 → (1)
2x - 5y = 13 → (2)
Subtracting (1) from (2) term by term will eliminate the x-0 term
0 - 5y - y = 13 - (- 5) , that is
- 6y = 18 ( divide both sides by - 6 )
y = - 3
Substitute y = - 3 into either of the 2 equations and solve for x
Substituting into (1)
2x - 3 = - 5 ( add 3 to both sides )
2x = - 2 ( divide both sides by 2 )
x = - 1
solution is (- 1, - 3 )
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.